2019
DOI: 10.3390/pr7090602
|View full text |Cite
|
Sign up to set email alerts
|

An Approach for Feedforward Model Predictive Control of Continuous Pulp Digesters

Abstract: Kappa number variability at the continuous digester outlet is a major concern for pulp and paper mills. It is evident that the aforementioned variability is strongly linked to the feedstock wood properties, particularly lignin content. Online measurement of lignin content utilizing near-infrared spectroscopy at the inlet of the digester is paving the way for tighter control of the blow-line Kappa number. In this paper, an innovative approach of feedforwarding the lignin content to a model predictive controller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Araneda et al [33] adapted the Purdue model to simulate an industrial Lo-Solids pulp digester and thus showed 9.1% savings of white liquor can be achieved by adapting operating conditions. Recently, Rahman et al [6] developed a dynamic continuous digester model for real-time simulation by following reaction kinetics similar to Bhartiya et al [29] and simplified compaction similar to Fernandes and Castro [15]. The authors developed an object-oriented modeling library in Modelica language [34] for modeling various commercial digesters.…”
Section: Purdue Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Araneda et al [33] adapted the Purdue model to simulate an industrial Lo-Solids pulp digester and thus showed 9.1% savings of white liquor can be achieved by adapting operating conditions. Recently, Rahman et al [6] developed a dynamic continuous digester model for real-time simulation by following reaction kinetics similar to Bhartiya et al [29] and simplified compaction similar to Fernandes and Castro [15]. The authors developed an object-oriented modeling library in Modelica language [34] for modeling various commercial digesters.…”
Section: Purdue Modelmentioning
confidence: 99%
“…The residence time between these points can be between four to six hours. This literally means that the instantaneous Kappa number measurement is a result of past process input parameters that existed four to six hours earlier [6]. Moreover, blow-line Kappa number is affected by a huge number of process variables.…”
Section: Kappa Number Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors presented an approach for predicting the kappa number using chemical reaction kinetics (Sixta and Rutkowska, 2007;Germgård, 2017), physical phenomena (Rantanen, 2006;Laakso, 2008), Near Infrared regression models (Monrroy et al, 2008;Santos et al, 2014, Moral et al 2015 or advanced process predictive model control tools (Badwe, 2016;Rahman et al, 2017).…”
Section: Kraft Pulping Modelingmentioning
confidence: 99%
“…Andersson et al 11 and Sixta et al 12 performed comparative analysis on the accuracy of these kinetic models, and concluded that the Purdue model has the best structure in both incorporating the process complexity and optimizing the computational efficiency. Motivated by the modeling efforts and tight regulations on product quality, the model predictive control (MPC) has been widely used for different types of pulp digesters, 13‐18 and these works have been extended to design plantwide control frameworks 19,20 …”
Section: Introductionmentioning
confidence: 99%